2019
DOI: 10.1007/978-3-030-28005-5_34
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Attacks and Security Requirements for Wireless Body Area Networks - A Systematic Literature Review

Abstract: Wireless Body Area Networks are gaining popularity in healthcare applications due to recent advances in sensor technology, integrated circuits, and wireless communication. These systems need to ensure that data is protected during collection, transmission, processing and storage. Currently, no complete solution exists for ensuring data is protected while also meeting regulatory security requirements for wireless body area network applications. To develop effective solutions, it is necessary to explore the atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Also, the authors analyzed the impact of network layer attacks in MANETs using Neural Networks in terms of bit error rate, throughput, e2e delay, and energy consumption [16], [17]. The authors presented a broad survey of routing protocols, applications, security challenges, requirements, and attacks [18]- [22]. Moreover, the authors analyzed the performance of the Denial-of-Service attack on the physical, data link, and transport layers in WBAN [23].…”
Section: Related Workmentioning
confidence: 99%
“…Also, the authors analyzed the impact of network layer attacks in MANETs using Neural Networks in terms of bit error rate, throughput, e2e delay, and energy consumption [16], [17]. The authors presented a broad survey of routing protocols, applications, security challenges, requirements, and attacks [18]- [22]. Moreover, the authors analyzed the performance of the Denial-of-Service attack on the physical, data link, and transport layers in WBAN [23].…”
Section: Related Workmentioning
confidence: 99%
“…• Integrity: When data is received, the receiver party has to ensure that the received information is original and have not been altered during the transmission phase [99]. Confidentiality measures cannot protect data from modification, which can be easily done by intercepting data in the transmission phase to inject, delete, or modify the sent message.…”
Section: Security In Wbanmentioning
confidence: 99%
“…These attacks make the security and privacy of PHR data one of the primary challenges for WBAN systems. We have previously conducted a structured literature review and identified a total of 11 types of attacks on WBAN applications, in addition to identifying 22 security and privacy requirements for WBAN applications [8].…”
Section: Background and Related Workmentioning
confidence: 99%
“…Each control was mapped to the WBAN security and privacy requirements that the authors had previously identified through a literature review, which is presented in [8]. Controls were then selected by excluding controls that related to: (1) Business operation, (2) Organizational facilities, (3) Management operation, (4) Offices, rooms and facilities, (5) Human resource security, (6) Personal security and (7) Network cabling.…”
Section: Control Selectionmentioning
confidence: 99%